Evaluation of Extracts Obtained from Fruit Wastes Using Different Methods - Florez Montes, Ciliana; Rojas González, Andrés Felipe; Rodríguez Barona, Sneyder (Ingeniería, 2020)
Context: Currently, the increase in agroindustrial waste generation has encouraged the search for viable use alternatives. In this paper, four methods to obtain extracts from mango, soursop, and grape peels, as well as and grape seeds, are studied. Their efficiency is analyzed through extraction yields and antioxidant capacity characterization of the extracts. Method: The extraction was performed using solvent, Soxhlet, microwave-assisted, and ultrasound assisted extraction. The characterization of the extracts was made by total phenolic compounds and flavonoids quantification, as well as antioxidant capacity determination, using the DPPH, FRAP, and ORAC tests. Results: It was found that grape seed extracts obtained by different extraction methods, highlighting those obtained by microwave assisted extraction, present a high total content phenolic compounds (>321.381,41 ± 3.476,85 μg Gallic Acid/g) and flavonoids (>103.232,01 ± 4.638,19 μg Quercetin/g), in addition to high antioxidant activity, according to the results of the DPPH (<1,06 ± 0,01), FRAP (>152.280,08 ± 5.197,53 µg TROLOX/g), and ORAC (>124.566,81 ± 581,96 μg TROLOX/g) tests. Conclusions: The results presented in this study suggest that the extracts obtained from grape seeds, especially those obtained by means of microwave-assisted extraction, have a potential use in food and pharmaceutical industries, due to their high antioxidant capacity and their total phenolic compounds and flavonoids content.